Penentu transparansi pemerintah daerah: sebuah studi pada pemerintah daerah di Indonesia - Muhtar Muhtar; Deni Ariyanto Putro; Sutaryo Sutaryo (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
We analysed transparency in 394 local government in Indonesia during 2012-2015 period using sociodemography, fiscal, institutional, and economy factors. Transparency is assessed from the result of transparency assessment on local government level from the Commission of Information for Indonesia (Komisi Informasi Indonesia). We use the ratio of elder and human development index as demographic factors; fiscal capacity and leverage as fiscal factors; ideology and the level of local government head vistory as institutional factors; and unemployment level and gross domestic product as economic factors. The data is analysed using panel data regressiong. The analysis result shows that the ratio of elder has negative effect on transparency, but the level of fiscal decentralization, leverage, ideology, unemployment, and economic activity has positive effect on local government transparency in Indonesia. Meanwhile, human resource development and the level of local government head victory have no effect on local government transparency. These results imply that local government needs to increase the level of fiscal decentralization and economic activity at the local government level, as well as reducing the number of unemployment to optimize the transparency in their local government. Future research should try using another transparency measurement such as transparency in local government website and using another factor such as local government environment.